HOXA10 improves endometrial receptivity by upregulating E-cadherin - Bi, Yin; Huang, Weiyu; Yuan, Lifang; Chen, Saiqiong; Liao, Shengbin; Fu, Xiaoqian; Liu, Bo; Yang, Yihua (Biology of reproduction, 2022)
In the endometrium of women with recurrent implantation failure and unexplained recurrent miscarriage, the expression levels of homeobox A10 and E-cadherin were positively correlated. To explore whether homeobox A10 regulates E-cadherin during endometrial receptivity establishment, Ishikawa and RL95-2 cells were transfected with target-specific small interfering RNA (siRNA) and overexpression plasmid of homeobox A10. The expression levels of homeobox A10 and E-cadherin were measured by western blot and quantitative Real-time Polymerase Chain Reaction (qRT-PCR). Attachment assay of JEG-3 spheroids to endometrial cells were conducted to explore the adhesive functions after homeobox A10 interfered. Chromatin immunoprecipitation assays and dual luciferase reporter were used to investigate the regulatory mechanism of homeobox A10. The CD1 mice were transfected with si-homeobox A10 to confirm these results in vivo. In Ishikawa and RL95-2 cells, the expression of E-cadherin was positively correlated with homeobox A10 when it was silenced/overexpressed. Consistently, the adhesion of endometrial epithelium cells and trophoblast cells was inhibited after homeobox A10 was silenced, and exogenous restoration of E-cadherin expression reversed this effect to some extent. Homeobox A10 regulates the expression of E-cadherin by directly binding to a conserved motif (TGTACTAAAAA) located in the E-cadherin promoter region. In addition, after knockdown of homeobox A10 in CD1 mice, both the implantation and live birth rates were decreased. In conclusion, homeobox A10 can bind to the E-cadherin promoter region and directly regulate its expression, thereby improving endometrial receptivity and subsequently increasing the embryo adhesion and implantation. Summary Sentence In conclusion, HOXA10 improves endometria receptivity by upregulating E-cadherin.